Empowered imagination and mental vulnerability: local theory of mind and spiritual experience in Vanuatu. (25th March 2020) - Smith, Rachel E.
Abstract: 'Theory of mind' in developmental psychology focuses on how children develop the ability to infer others' beliefs, desires, and intentions. Anthropologists have taken up the notion of 'theory of mind' to explore the way cultural differences in representations of beliefs, desires, and intentions affect everyday lives. In Oceania, anthropologists have noted that inferences about others' intentions are not accorded a privileged role in social interaction. In Vanuatu, I find, it is often the material, rather than immaterial, aspects of relatedness that are elaborated upon. People think about knowledge, creativity, meaning, and intention not as confined to a bounded mental or inner domain, but as discoverable through the body, and in the world at large. I argue here that this propensity to locate meaning and moral purpose as external to the mind corresponds to a 'porous' view of self and mind, and that this in turn may open people to experience vivid, intense, and often tangible forms of spiritual encounter. Abstrait: Imagination agissante et vulnérabilité mentale : théorie locale de l'esprit et expérience spirituelle au Vanuatu Résumé En psychologie du développement, la « théorie de l'esprit » décrit la manière dont les enfants développent la capacité de deviner les croyances, désirs et intentions des autres. Les anthropologues ont repris cette notion pour explorer la manière dont les différences culturelles de représentation des croyances, des désirs et des intentions affectent la vie quotidienne. En Océanie, ils ont remarqué que la déduction des intentions de l'autre ne jouait pas un rôle privilégié dans les interactions sociales. Au Vanuatu, ce sont souvent les aspects matériels des liens, plutôt que les aspects immatériels, qui sont développés. La connaissance, la créativité, la signification et l'intention n'y sont pas confinées à un domaine mental ou intérieur délimité mais peuvent être découvertes à travers le corps et, plus largement, dans le monde. L'autrice avance que cette propension à situer la signification et le but moral à l'extérieur de l'esprit correspond à une vision « poreuse » de soi‐même et de l'esprit, ce qui peut ouvrir à des rencontres spirituelles vivaces, intenses et souvent tangibles.